The Fault Tree Analysis of Causes of the Welded Pipes Failures in Exploitation - Nikolic, Ruzica; Arsic, Dusan; Arsic, Aleksandra; Sarkocevic, Zivce; Cvetkovic, Dragan; Hadzima, Branislav (Communications - Scientific Letters of the University of Zilina, 2020)
Premature failure or damage of parts and components of the oil and gas well piping, as well as pipelines for transport of oil and gas, are generally caused by the simultaneous influence of a large number of technological, metallurgical, structural and exploitation factors. Therefore, the convenient structural solutions, which provide the mechanical safety of parts and integrity of structures, can be realized only through total comprehension of their behavior in various operation regimes. Importance of technical diagnostics for monitoring and state analysis of welded pipes/pipelines in oil industry is considered in this paper. An analysis of causes of the welded pipes failures in exploitation has been performed through use of the fault tree analysis. Based on the suggested structure of a database, regarding the causes of failure, possibilities are presented to set measures for prevention of damage and failure of welded pipes/pipelines and for extension of their service life. A suggestion for improvement of the organizational scheme for monitoring the state and maintenance of welded pipes/pipelines during the exploitation has been made, as well.
Keywords: welded pipes; damage; failure; the fault tree; database; preventive measures